Preserving Islamic Culture in the Digital Era A KPI-Driven Framework for Waqf Transformation and Cultural Sustainability - SeyyedAbdolHojjat MoghadasNian; MoghadasNian, AqilaSadat; Karami, Fatemeh (6th International Conference on Management Studies, Culture & Art, 2025)
This study examines the role of Key Performance Indicators (KPIs) in guiding digital transformation within Waqf institutions, emphasizing their application in preserving Islamic cultural heritage. By establishing a KPI-driven framework, Waqf organizations can systematically assess and enhance the impact of digital initiatives, ensuring alignment with core preservation objectives. Key KPIs including Digital Engagement Rate, Content Accessibility Index, Donor Retention Rate, and Asset Digitization provide actionable metrics for tracking progress, optimizing resource use, and fostering cultural sustainability. Through case studies, this research highlights effective digital tools such as blockchain for transparency and AI-enhanced content curation, which collectively support both heritage preservation and broader global access. The findings underscore the need for regionally tailored KPI strategies to address digital infrastructure disparities. Overall, the research suggests that a KPI-focused approach equips Waqf institutions to embrace modern technology while strengthening their cultural mission in an evolving digital landscape.